Between Necessity and Legal Responsibility: The Development of EEWS in Italy and its International Framework - Valbonesi, Cecilia (Frontiers in Earth Science, 2021)
Earthquake Early Warning Systems (EEWSs) represent a technical-scientific challenge aimed at improving the chance of the population exposed to the earthquake shaking of surviving or being less affected. The ability of an EEWS to affect the risk and, in particular, vulnerability and exposure, may determine serious legal responsibilities for people involved in the system, as scientists and experts. The main question concerns, in fact, the relationship between EEWSs and the predictability and avoidability of earthquake effects-i.e., the ground shaking affecting citizens and infrastructures - and the possibility for people to adopt self-protective behavior and/or for industrial infrastructures to be secured. In Italy, natural disasters, such as the 2009 L’Aquila earthquake, teach us that the relationship between science and law is really difficult. So, before EEW’s become operational in Italy, it is necessary to: 1) examine the legislative and technical solutions adopted by some of the international legal systems in countries where this service is offered to citizens; 2) reconstruct the international and European regulatory framework that promotes the introduction of EW systems as life-saving tools for the protection of the right to life and understand whether and how these regulatory texts can impose an obligation on the Italian legal system to develop EEWS; 3) understand what responsibilities could be ascribed to the scientists and technicians responsible for managing EEWS in Italy, analyzing the different impact of vulnerability and exposure on the predictability and avoidability of the harmful event; 4) reflect on the lessons that our legal system will have to learn from other Countries when implementing EEW systems. In order to find appropriate solutions, it is essential to reflect on the opportunity to provide shared and well-structured protocols and creating detailed disclaimers clearly defining the limits of the service. A central role must be recognized to education, because people should not only expect to receive a correct alarm but must be able to understand the uncertainties involved in rapid estimates, be prepared to face the risk, and react in the right way.